Newly diagnosed HIV and use of HIV-PrEP among non-western born MSM attending STI clinics in the Netherlands: a large retrospective cohort study - Evers, Ymke J.; Goense, Cornelia J. D.; Hoebe, Christian J. P. A.; Dukers-Muijrers, Nicole H. T. M. (Frontiers in Public Health, 2023)
Introduction The World Health Organization recommends HIV-PrEP for all people at risk for HIV infection, which includes men who have sex with men (MSM). Substantial part of new HIV diagnoses in the Netherlands are in non-western born MSM. This study evaluated new HIV diagnoses and reported PrEP use among non-western born MSM and compared it to western-born MSM. To inform public health efforts in the context of equitable PrEP access, we further assessed sociodemographic factors related to higher HIV risk and lower PrEP use among non-western born MSM. Methods Surveillance data of consultations among MSM in all Dutch STI-clinics (2016–2021) were analyzed. STI-clinics provide PrEP via the national pilot-program since August 2019. In non-western born MSM (born in Eastern-Europe/Latin-America/Asia/Africa/Dutch-Antilles/Suriname), sociodemographic factors were evaluated for association with HIV (by multivariable generalized estimating equations) and reported PrEP use in the past 3 months (by multivariable logistic regression; restricted to an at-risk for HIV person-level data-subset from August 2019). Results New HIV infections were diagnosed among 1.1% (493/44,394) of non-western born MSM-consultations (vs. 0.4% among western-born MSM, 742/210,450). Low education (aOR: 2.2, 95%CI: 1.7–2.7, vs. high education) and age under 25 years (aOR: 1.4, 95%CI: 1.1–1.8, vs. age above 35 years) were associated with new HIV diagnoses. PrEP use in the past 3 months was 40.7% in non-western born MSM (1,711/4,207; 34.9% among western-born MSM, 6,089/17,458). PrEP use was lower among non-western born MSM aged under 25 years (aOR: 0.3, 95%CI: 0.2–0.4), living in less urban areas (aOR: 0.7, 95%CI: 0.6–0.8), and having low education level (aOR: 0.6, 95%CI: 0.5–0.7). Conclusion Our study confirmed that non-western born MSM are an important key population in HIV prevention. Access to HIV prevention, including HIV-PrEP, should be further optimized to all non-western born MSM at risk for HIV, and specifically to those who are younger, live in less urban areas, and have a low education level.